Education for sustainable development : challenges, strategies, and practices in a globalizing world - Nikolopoulou, Anastasia; Abraham, Taisha; Mirbagheri, Farid (New Delhi, India : Thousand Oaks, Calif: Sage, 2010)
Explores sustainable development as a process that embraces environmental issues, poverty, health, security, democracy, gender and human rights. This collection provides multiple perspectives regarding the possibility of creating sustainable education practices that are integrated into and relevant to the needs and practices on a global scale.
Includes bibliographical references and index.
Keywords: Environmental education; Sustainable development; World citizenship; Education -- Social aspects